2017
DOI: 10.1177/2055217317730098
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of neuromyelitis optica in Latin America

Abstract: A major development over the past two decades was the recognition of recurrent neuromyelitis optica (NMO) as a particular central nervous system disorder different from multiple sclerosis (MS). Here we reviewed the epidemiology of NMO in Latin America (LATAM). A predominance of a mixed population is found in this region. Recurrent NMO in black women was described in the Caribbean Islands and in Rio de Janeiro. The prevalence of NMO in LATAM varied from 0.37/100,000 (Volta Redonda city) to 4.2/100,000 inhabitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 39 publications
(62 reference statements)
3
29
0
3
Order By: Relevance
“…Notably, local ancestry analyses revealed that all HLA alleles most associated with NMO risk and protection in the present study were predominantly inferred as of Native American ancestry. This is consistent with our finding of a higher proportion of NAT ancestry in NMO cases as compared to controls, and with epidemiological data suggesting that NMO is more prevalent in non-European populations [9][10][11] . To our knowledge there is only one previous study analyzing local ancestry of demyelinating diseases, where HLA alleles DRB1*16:02 and DRB1*14:02 were inferred as of Native American ancestry in Hispanics 43 , also in consistency with our local ancestry findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Notably, local ancestry analyses revealed that all HLA alleles most associated with NMO risk and protection in the present study were predominantly inferred as of Native American ancestry. This is consistent with our finding of a higher proportion of NAT ancestry in NMO cases as compared to controls, and with epidemiological data suggesting that NMO is more prevalent in non-European populations [9][10][11] . To our knowledge there is only one previous study analyzing local ancestry of demyelinating diseases, where HLA alleles DRB1*16:02 and DRB1*14:02 were inferred as of Native American ancestry in Hispanics 43 , also in consistency with our local ancestry findings.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the relative frequency of NMO (estimated as the ratio of NMO/(MS + NMO) cases) has been found to decrease gradually in South America from North (Venezuela) to South (Argentina). Because ethnicity also changes gradually from North to South in this region, with the proportion of European individuals being lower in Venezuela and higher in Argentina, the authors suggested that ethnic origin influences NMO frequency in Latin America 10 . To date there are no population-based studies of the prevalence of NMO in Mexico, and there is a single study estimating NMO prevalence at 1.3 per 100,000 inhabitants based on the NMO/(MS + NMO) relative frequency at a referral center in Mexico City 12 .…”
mentioning
confidence: 99%
“…A noteworthy exception to our finding of overall lower seroprevalence of AQP4-IgG seropositivity in non-Asian populations was the study by Carnero-Contentti et al ( 39 ), which enrolled patients from Buenos Aires, Argentina, and reported an AQP4-IgG seroprevalence of 30% among patients with ON ( 39 ). This finding is unexpected, given evidence supporting that the relative frequency of NMO vs. MS in Buenos Aires is low, and similar to that observed in Caucasian populations ( 91 ). Notably, this study did not report the ethnic/racial composition of the cohort, and it is possible that referral bias or other factors, which we were unable to detect on our review of the manuscript, contributed to this observation.…”
Section: Discussionmentioning
confidence: 55%
“…2,3 Previous epidemiological studies have suggested that NMOSD is less frequent in Caucasian populations compared to Asian, African and Latin American populations. [4][5][6][7][8] However, the number of large, population-based epidemiological studies is still scarce, and none is available from Eastern Europe.…”
Section: Introductionmentioning
confidence: 99%